Enhancing security of incoherent optical cryptosystem by a simple position-multiplexing technique and ultra-broadband illumination. Issue 1 (December 2017) - Sahoo, Sujit; Tang, Dongliang; Dang, Cuong
Abstract A position-multiplexing technique with ultra-broadband illumination is proposed to enhance the information security of an incoherent optical cryptosystem. This simplified optical encryption system only contains one diffuser acting as the random phase mask (RPM). Incoherent light coming from a plaintext passes through this nature RPM and generates the corresponding ciphertext on a camera. The proposed system effectively reduces problems of critical alignment sensitivity and coherent noise that are found in the coherent illumination. Here, the use of ultra-broadband illumination has the advantage of reducing the speckle contrast that makes the ciphertext more complex. Reduction of the ciphertext size further increases the strength of the ciphering. Using the spatial decorrelation of the speckle pattern we have demonstrated a position multiplexed based cryptosystem, where the ciphertext is the superposition of uniquely encrypted texts from various spatial positions. These unique spatial keys are utilized to decrypt the plaintext located at different spatial positions, and a complete decrypted text can be concatenated with high fidelity. Benefiting from position-multiplexing, the information of interest is scrambled together by a truly random method in a smaller ciphertext. A high performance security for an optical cryptosystem has been achieved in a simple setup with a ground glass diffuser as a nature RPM, the broadband incoherent illumination and small position-multiplexed ciphertext.